In-flight transmission of SARS-CoV-2: a review of the attack rates and available data on the efficacy of face masks - Freedman, David O (J Travel Med, 2020)
The absence of large numbers of published in-flight transmissions of SARS-CoV-2 is not definitive evidence of safety. All peer-reviewed publications of flights with possible transmission are categorized by the quantity of transmission. Three mass transmission flights without masking are contrasted to 5 with strict masking and 58 cases with zero transmission.